A QSAR study to predict the survival motor neuron promoter activity of candidate diaminoquinazoline derivatives for the potential treatment of spinal muscular atrophy - ERDEM, SAFİYE (My University, 2023)
Spinal Muscular Atrophy is a genetic neuromuscular disease that leads to muscle weakness and atrophy and it is characterized by the loss of α-motor neurons in the spinal cord\"s anterior horn cells. The disease appears due to low levels of the survival motor neuron protein. There are continuing clinical trials for the treatment of Spinal Muscular Atrophy. Quinazoline-based compounds are promising since they were tested on fibroblasts derived from the patients and found to increase the survival motor neuron protein levels. In this study, using multiple linear regression, we generated robust and valid quantitative structure- activity relationship models to predict the survival motor neuron-2 promoter activity of the new candidate compounds using the experimental survival motor neuron-2 promoter activity values of 2,4-diaminoquinazoline derivatives taken from the literature. The novel compounds designed by combining the pyrido[1,2-α]pyrimidin-4-one moeity of the known drug Risdiplam with that of 2,4 - diaminoquinazoline scaffold were predicted to exhibit strong promoter activities.
Keywords: Biyomedikal Mühendisliği; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Mühendislik ve Teknoloji; Biomedical Engineering; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Yaşam Bilimleri (LIFE); Mühendislik; Mikrobiyoloji; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; MÜHENDİSLİK, BİYOMEDİKAL; Engineering, Computing & Technology (ENG); Life Sciences (LIFE); ENGINEERING; MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; ENGINEERING, BIOMEDICAL; Biyomühendislik; Fizik Bilimleri; Moleküler Tıp; İlaç Keşfi; Bioengineering; Physical Sciences; Molecular Medicine; Drug Discovery; diaminoquinazoline; MLR; QSAR; Risdiplam; SMA; SMN protein